2019
DOI: 10.5435/jaaos-d-17-00764
|View full text |Cite
|
Sign up to set email alerts
|

C5 Motor Palsy After Single- and Multi-level Anterior Cervical Diskectomy and Fusion: A Retrospective Review

Abstract: Introduction: Postoperative C5 nerve root palsy is a known complication after cervical surgery. The effect of increasing number of levels fused on the prevalence of C5 palsy after anterior cervical diskectomy and fusion (ACDF) is unclear. Methods: Medical records of ACDF patients that included the C4-5 level at one institution were retrospectively reviewed. C5 palsy was defined as motor decline of the deltoid and/or biceps brachii muscle function by at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Abnormal electromyogram results indicated that the patient had subclinical nerve root compression, which was the pathological basis for the occurrence of C5P. Although numerous previous studies have shown that preoperative and postoperative JOA scores were not independent predictors of C5P, something interesting was observed in this study [32][33][34][35][36]. The JOA recovery rate was significantly higher in the C5P group than in the No C5P group and was identified as an independent risk factor for C5P.…”
Section: Discussionmentioning
confidence: 40%
“…Abnormal electromyogram results indicated that the patient had subclinical nerve root compression, which was the pathological basis for the occurrence of C5P. Although numerous previous studies have shown that preoperative and postoperative JOA scores were not independent predictors of C5P, something interesting was observed in this study [32][33][34][35][36]. The JOA recovery rate was significantly higher in the C5P group than in the No C5P group and was identified as an independent risk factor for C5P.…”
Section: Discussionmentioning
confidence: 40%
“…Although numerous previous studies have shown that preoperative, and postoperative JOA scores were not independent predictors of C5P, something interesting was observed in this study. [33][34][35][36][37] The JOA recovery rate was signi cantly higher in C5P group than that in the no-C5P group and was identi ed as an independent risk factor for C5P. In our clinical practice, the majority of patients with C5P had a good prognosis without speci c treatment.…”
Section: Discussionmentioning
confidence: 95%